L1 integration in a transgenic mouse model - Babushok, Daria V.; Ostertag, Eric M.; Courtney, Christine E.; Choi, Janice M.; Kazazian, Haig H. (Genome Research, 2006)
To study integration of the human LINE-1 retrotransposon (L1) in vivo, we developed a transgenic mouse model of L1 retrotransposition that displays de novo somatic L1 insertions at a high frequency, occasionally several insertions per mouse. We mapped 3′ integration sites of 51 insertions by Thermal Asymmetric Interlaced PCR (TAIL–PCR). Analysis of integration locations revealed a broad genomic distribution with a modest preference for intergenic regions. We characterized the complete structures of 33 de novo retrotransposition events. Our results highlight the large number of highly truncated L1s, as over 52% (27/51) of total integrants were <1/3 the length of a full-length element. New integrants carry all structural characteristics typical of genomic L1s, including a number with inversions, deletions, and 5′-end microhomologies to the target DNA sequence. Notably, at least 13% (7/51) of all insertions contain a short stretch of extra nucleotides at their 5′ end, which we postulate result from template-jumping by the L1-encoded reverse transcriptase. We propose a unified model of L1 integration that explains all of the characteristic features of L1 retrotransposition, such as 5′ truncations, inversions, extra nucleotide additions, and 5′ boundary and inversion point microhomologies.